USING STATISTICAL TESTS MODELS TO FIND OUT THE EXTENT TO WHICH INCOME AND BALANCE SHEET ELEMENTS ARE AFFECTED IN UNDER OF THE RISKS OF COVID 19, AN ANALYTICAL STUDY IN IRAQI COMPANIES (World Economics and Finance Bulletin, 2023)
The research mainly aims to find out the extent to which there is an effect on the income and budget elements of the research sample company through the decline in business results and financial position due to its exposure to the risks of Covid 19 and the results of uncertainty resulting from those risks. Modern clothing is one of the industrial sector companies listed in the Iraqi Stock Exchange, and the research concluded that the risks of Covid 19 greatly affected the income and budget components of the modern clothing company between the decrease represented by the loss and the increase represented by incurring other additional costs to reduce these risks, and the researcher recommends that a Activate the risk management and analysis policy in each company to limit or reduce the effects of any future risks